Born Out of Place : Migrant Mothers and the Politics of International Labor - Constable, Nicole (Book collections on Project MUSE., 2014)
Hong Kong is a meeting place for migrant domestic workers, traders, refugees, asylum seekers, tourists, businessmen, and local residents. In Born Out of Place, Nicole Constable looks at the experiences of Indonesian and Filipina women in this Asian world city. Giving voice to the stories of these migrant mothers, their South Asian, African, Chinese, and Western expatriate partners, and their Hong Kong-born babies, Constable raises a serious question: Do we regard migrants as people, or just as temporary workers? This accessible ethnography provides insight into global problems of mobility, family, and citizenship and points to the consequences, creative responses, melodramas, and tragedies of labor and migration policies.